'Unconscionability' and the case against lumping: three case studies. Issue 1 (28th December 2020) - Liew, Ying Khai
Abstract: This article argues that unconscionability provides no good basis for arguments in favour of lumping equitable doctrines in English law. It explores three areas of equity where unconscionability has most strongly divided lumpers and splitters: undue influence and unconscionable bargains; proprietary estoppel and constructive trusts; and the 'rule in Re Rose ' and the decision in Pennington v Waine . In relation to each discussion, the paper explains how lumpers rely on the idea of unconscionability to argue in favour of merging or expanding those established doctrines, and argues against lumping, by explaining how this distorts a proper understanding of the law.